2020
DOI: 10.1038/s41598-020-63903-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Rotational Angiography during Catheterization of Congenital Heart Disease – A ten Years’ experience at a single center

Abstract: this paper aims to assess the usability and advantages of three-dimensional rotational angiography (3DRA) in patients with congenital heart disease (CHD) and its application in the cath lab. Up to now, its use in CHD is not widespread or standardized. We analyzed all patients with CHD who underwent a 3DRA at our facility between January 2010 and May 2019. The 3DRAs were evaluated for radiation exposure, contrast dye consumption, diagnostic utility and image quality. We performed 872 3DRAs. 3DRA was used in 67.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Some studies show higher radiation exposure with 3DRA, yet more recent research suggests lower values when using optimized exposure settings for the 3DRA imaging protocol. Some authors argue that diagnostic 3DRA is outdated for primary diagnosis and 3D guidance due to the availability of MMIF 2D−3D ( 24 , 36 ). However, it remains valuable when preprocedural imaging is not possible ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show higher radiation exposure with 3DRA, yet more recent research suggests lower values when using optimized exposure settings for the 3DRA imaging protocol. Some authors argue that diagnostic 3DRA is outdated for primary diagnosis and 3D guidance due to the availability of MMIF 2D−3D ( 24 , 36 ). However, it remains valuable when preprocedural imaging is not possible ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors argue that diagnostic 3DRA is outdated for primary diagnosis and 3D guidance due to the availability of MMIF 2D−3D ( 24 , 36 ). However, it remains valuable when preprocedural imaging is not possible ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Appreciation of concomitant lesions has improved with the application of three-dimensional imaging modalities such as angiographic computed tomography and traditional computed tomography, which can provide a definitive anatomical diagnosis of undiscovered lesions [12]. Recent studies have demonstrated growing trends in using three-dimensional rotational angiographies, which has been associated with superior outcomes in diagnostic and interventional procedures [13,14]. Hybrid procedures, initially intended for initial palliation of the hypoplastic left heart and complex single ventricle, have now been expanded to address septal defects and stenotic pulmonary arteries.…”
Section: Discussionmentioning
confidence: 99%